Structure Optimization of Gas-Liquid Separator Based on STAR CCM+. Issue 4 (March 2020) - Liang, Qiufeng; Xiao, Changrun; Zhang, Lu; He, Senlin
Abstract: At present, most of the submarine air compressors at home and abroad are directly discharged into the cabin when they blow off the condensed water and oil, resulting in environmental pollution in the cabin and corrosion of surrounding parts. In order to solve this problem, this paper studies the condensate drain device of submarine air compressor. STAR CCM + based on CFD method is adopted to analyze the flow field of two-phase gas-liquid separator. The reliability of STAR CCM + numerical simulation is verified by comparing with the existing test data [1]. On this foundation, combined with submarine cabin space and condensate discharge characteristics of submarine air compressor, the structure of gas-liquid separator is optimized. Focus on the analysis of flow field distribution and gas-liquid separation effect in the case of different baffles and the presence or absence of baffles. The results show that when the inlet dryness is 0.7, the bottom baffle of the separator can make the internal flow field more stable; the dryness of separator gas outlet can reach 0.99 with four-turn spiral deflector and the bottom mounted baffle. The result of numerical simulation can provide a valuable reference for the design of the condensate drain device of submarine air compressor.